Adiponectin Expression in the Porcine Ovary during the Oestrous Cycle and Its Effect on Ovarian Steroidogenesis - Anna Maleszka; Nina Smolinska; Anna Nitkiewicz; Marta Kiezun; Katarzyna Chojnowska; Kamil Dobrzyn; Hubert Szwaczek; Tadeusz Kaminski (International Journal of Endocrinology)
Adiponectin is an adipose-secreted hormone that regulates energy homeostasis and is also involved in the control of the reproductive system. The goal of the present study was to investigate changes in adiponectin gene and protein expression in porcine ovarian structures during the oestrous cycle and to examine the effects of in vitro administration of adiponectin on basal and gonadotrophin- and/or insulin-induced secretion of ovarian steroid hormones. Both gene and protein expression of adiponectin were enhanced during the luteal phase of the cycle. Adiponectin affected basal secretion of progesterone by luteal cells, oestradiol by granulosa cells, and testosterone by theca interna cells. The gonadotrophin/insulin-induced release of progesterone from granulosa and theca interna cells and the release of oestradiol and androstenedione from theca cells was also modified by adiponectin. In conclusion, the presence of adiponectin mRNA and protein in the porcine ovary coupled with our previous results indicating adiponectin receptors expression suggest that adiponectin may locally affect ovarian functions. The changes in adiponectin expression throughout the oestrous cycle seem to be dependent on the hormonal status of pigs related to the stage of the oestrous cycle. The effect of adiponectin on ovarian steroidogenesis suggests that this adipokine influences reproductive functions in pigs.